The ability of waist-to-height ratio to identify health risk - Márcia Mara Corrêa; Luiz Augusto Facchini; Elaine Thumé; Elizabete Regina Araújo de Oliveira; Elaine Tomasi
ABSTRACT OBJECTIVE To evaluate the performance of the ratio between the waist circumference and the height in the identification of health risk compared with the correlation matrix between the anthropometric parameters body mass index and waist circumference. METHODS A population-based study presenting a transversal cut in a representative sample of the Brazilian adult and older population. The combination of the body mass index with the waist circumference resulted in health risk categories, and the cutoff points of the ratio between the waist circumference and the height as anthropometric indicator were used for classification of low and increased risk. Poisson regression was used to verify the association of systemic arterial hypertension with the health risk categories. RESULTS The results showed 26% of adult men, 10.4% of adult women and more than 30% of the older adults of both genders classified as without risk by the combination matrix between body mass index and waist circumference presented a ratio between the waist circumference and height that showed increased risk. All risk categories continued to be associated with hypertension after control for confounding factors, being almost two times higher for adults with moderate and high risk according to both methods. When the waist-to-height ratio was used as a risk indicator, the prevalence of hypertension ratios for the older adults was 1.37 (95%CI 1.16-1.63) and 1.35 (95%CI 1.12-1.62) for men and women, respectively, being these values close to the combination matrix body mass index and waist circumference. CONCLUSIONS The waist-to-height ratio identified more individuals at early health risk than the combination matrix between the body mass index and the waist circumference and showed comparable ability to identify health risk, regardless of gender and age, regarding the prevalence ratios for systemic arterial hypertension.